Momentum, Reversals, and Investor Clientele. (16th February 2022) - Chui, Andy C W; Subrahmanyam, Avanidhar; Titman, Sheridan
Abstract: Different share classes on the same firms provide a natural experiment to explore how investor clienteles affect momentum and short-term reversals. Domestic retail investors have a greater presence in Chinese A shares and foreign institutions are relatively more prevalent in B shares. These differences result from currency conversion restrictions and mandated investment quotas. We find that only B shares exhibit momentum and earnings drift and only A shares exhibit monthly reversals. Institutional ownership strengthens momentum in B shares. These patterns accord with a setting where short-term reversals (which represent inventory risk premia) prevail in a market dominated by noise traders and momentum prevails in markets where noise traders are less prevalent relative to informed investors who underreact to fundamental signals. Overall, our findings confirm that clienteles matter in generating stock return predictability from past returns.